Strategy and Efficacy of Surgery for Congenital Cervicothoracic Scoliosis with or without Hemivertebra Osteotomy. Issue 9 (30th August 2022) - Zhang, Hong‐qi; Du, Yu‐xuan; Liu, Jin‐yang; Deng, Ang; Wu, Jian‐huang; Wang, Yu‐xiang; Guo, Chao‐feng
Abstract : Objective: Cervicothoracic scoliosis will cause severe deformities in the early stage, and its structure is complex and the surgical methods are varied. The purpose of this research is to explore the indication and analyze the corrective effect of the two different posterior approach surgical strategies, including correction with fusion and hemivertebra osteotomy, for congenital cervicothoracic scoliosis deformities in children and adolescents. Methods: This was a retrospective study of 21 patients with cervicothoracic scoliosis who received surgical treatment from January 2010 to June 2020, including nine cases of posterior hemivertebra osteotomy and fusion surgery and 12 cases of posterior correction and fusion alone. The Cobb angle, T1 tilt angle, clavicular angle, neck tilt angle, radiographic shoulder height, sagittal vertical axis, coronal balance distance, and local kyphosis angle were measured preoperatively, postoperatively, and at the last follow‐up. Posterior approach hemivertebra resection or correction with fusion surgery was adopted based on the different individual characteristics of deformity such as main curve Cobb angle, growth potential, and flexibility. Patients were divided into two groups (osteotomy group and nonosteotomy group) according to whether a hemivertebra osteotomy was performed, and the corrective results in the two groups were compared. Paired‐sample t tests or independent‐sample t tests were used. Results: The median follow‐up after surgery of the 21 patients was 36 months (range, 18–72 months). The Cobb angle was corrected from 45.81° ± 14.23° preoperatively to 10.48° ± 5.56° postoperatively (correction rate, 77.78% ± 8.93%). The T1 tilt angle decreased from 15.26° ± 7.08° preoperatively to 3.33° ± 2.14° postoperatively (correction rate, 73.42% ± 21.86%). The radiographic shoulder height was corrected from 1.13 ± 0.74 cm preoperatively to 0.52 ± 0.42 cm postoperatively (correction rate, 39.51% ± 35.65%). The clavicular angle improved from 2.52° ± 1.55° preoperatively to 1.16° ± 0.96° postoperatively (correction rate, 47.18% ± 35.84%). No significant differences were found at the last follow‐up ( p > 0.05). The Cobb angle of the main curve, T1 tilt angle, clavicular angle, cervical tilt angle, and shoulder height difference were similar in the two groups ( p > 0.05). Conclusions: Posterior approach hemivertebra resection or correction with fusion surgery can be used in the treatment of congenital cervicothoracic scoliosis with satisfactory results, and the surgeon can make an individualized surgical plan according to individual characteristics of deformity. Abstract : A 12‐year‐old boy with C7 hemivertebra and multiple malformations in the lower spine underwent a C7 hemivertebra osteotomy and internal fixation from C5‐T3 via one‐stage posterior surgery. (A) preoperative X‐ray; (B) preoperative CT; (C, D) The C7 hemivertebra was resected by posterior approach surgery; (E, F) X‐ray at the 2‐year follow‐up.